2021
DOI: 10.1007/s00259-021-05507-9
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the cortex/striatum metabolic ratio on [18F]-FDG PET: a biomarker of autoimmune encephalitis

Abstract: Purpose: The aim of this 18 F-FDG PET study was to determine the diagnostic value of the cortex/striatum metabolic ratio in a large cohort of patients suffering from autoimmune encephalitis (AE) and to search for correlations with the course of the disease. Methods:We retrospectively collected clinical and paraclinical data of patients with AE, including brain 18 F-FDG PET/CT. Whole-brain statistical analysis was performed using SPM8 software after activity parametrization to the striatum in comparison to heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
(107 reference statements)
0
9
0
1
Order By: Relevance
“…As emerging data have demonstrated specific brain PET patterns in some NORSE etiologies (e.g. autoimmune encephalitis), 62 the indications for PET, in particular in the postacute phase, may increase in the future. Malignancy screening (computed tomography [CT] of chest, pelvis, and abdomen) should be performed in a majority of patients with cryptogenic NORSE/FIRES (M = 9, MA = 9, MP = 7.5, LA = 77.1%, LD = 4.2%).Malignancy screening should be considered in the diagnostic workup in all patients with cryptogenic NORSE but is of particular importance in adults, as the prevalence of paraneoplastic etiologies is substantially lower in children 7 Malignancy screening should include whole body PET when other testing, including CT of chest, pelvis, and abdomen, remains negative (M = 8, MA = 8, MP = 7, LA = 89.2%, LD = 2.7%).In a recent review on NORSE that included 197 publications, whole body PET was performed in 4.6% of patients 7 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As emerging data have demonstrated specific brain PET patterns in some NORSE etiologies (e.g. autoimmune encephalitis), 62 the indications for PET, in particular in the postacute phase, may increase in the future. Malignancy screening (computed tomography [CT] of chest, pelvis, and abdomen) should be performed in a majority of patients with cryptogenic NORSE/FIRES (M = 9, MA = 9, MP = 7.5, LA = 77.1%, LD = 4.2%).Malignancy screening should be considered in the diagnostic workup in all patients with cryptogenic NORSE but is of particular importance in adults, as the prevalence of paraneoplastic etiologies is substantially lower in children 7 Malignancy screening should include whole body PET when other testing, including CT of chest, pelvis, and abdomen, remains negative (M = 8, MA = 8, MP = 7, LA = 89.2%, LD = 2.7%).In a recent review on NORSE that included 197 publications, whole body PET was performed in 4.6% of patients 7 .…”
Section: Resultsmentioning
confidence: 99%
“…As emerging data have demonstrated specific brain PET patterns in some NORSE etiologies (e.g. autoimmune encephalitis), 62 the indications for PET, in particular in the postacute phase, may increase in the future. Malignancy screening (computed tomography [CT] of chest, pelvis, and abdomen) should be performed in a majority of patients with cryptogenic NORSE/FIRES (M = 9, MA = 9, MP = 7.5, LA = 77.1%, LD = 4.2%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that the ratio of patients with AE was significantly lower than that of patients with mild cognitive impairment and healthy controls. 42 FDG-PET scan has also revealed striatal hypermetabolism assessed qualitatively and semi-quantitatively, with normal uptake in the cortex and cerebellum in a case of VGKCC limbic encephalitis. 43 Putaminal standardized uptake value ratios (SUVRs) normalized to global brain (P), thalamus (P/Th), and midbrain (P/Mi) were also used to evaluate for diagnostic accuracy.…”
Section: Quantitative Fdg -Pe T Analys E Smentioning
confidence: 97%
“…Another study regarded cortex/striatum ratio in the voxel‐based analysis of FDG‐PET as a biomarker to uncover metabolism changes. The result showed that the ratio of patients with AE was significantly lower than that of patients with mild cognitive impairment and healthy controls 42 . FDG‐PET scan has also revealed striatal hypermetabolism assessed qualitatively and semi‐quantitatively, with normal uptake in the cortex and cerebellum in a case of VGKCC limbic encephalitis 43 .…”
Section: Quantitative Fdg‐pet Analysesmentioning
confidence: 99%